Effects of conformational constraint in 2- and 8-cycloleucine analogues of oxytocin and [1-penicillamine] oxytocin examined by circular dichroism and bioassay - Fric, I; Hlavacek, J; Rockway, T W; Chan, W Y; Hruby, V J (Journal of protein chemistry, 1990)
The analogues of oxytocin and [1-penicillamine]oxytocin, containing a cycloleucine (Cle) residue in position 2 or 8, were investigated by means of circular dichroism measurements in different solvents, and the results examined in terms of their biological activities. A cycloleucine residue in position 2 substantially reduces the free conformational space of the hormone 20-membered ring moiety (including the disulfide group), and stabilizes a conformation which is close to one of the possible conformations of oxytocin and involves a beta-turn. In position 8, the Cle residue affects the conformation of the Tyr2 side chain, apparently forcing it away from the space above the 20-membered disulfide ring. However, it does not appear that the Cle residue has any significant effect on the overall backbone conformation of the hormone. The steric effect of the penicillamine residue in position 1 on the conformation of the disulfide group and Tyr2 side chain from previous investigations is further confirmed. The synthesis and biological potency of [1-penicillamine, 8-cycloleucine]oxytocin is described. This analogue exhibits a strong inhibitory effect on the uterotonic activity of oxytocin in vitro. It also inhibited the vasopressor response to vasopressin.
Keywords: uterus; techniky in vitro; Oxytocin; biotest; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; oxytocin; Circular Dichroism; cykloleucin; Female; Protein Conformation; krysa rodu Rattus; zvířata; Uterus; Oxytocics; Penicillamine; cirkulární dichroismus; ženské pohlaví; Biological Assay; uterotonika; penicilamin; In Vitro Techniques; Rats; Animals; Cycloleucine; konformace proteinů